Chondrosarcoma from chondroblastoma in young: A rare event (Indian Journal of Case Reports, 2024)
Among bone tumors, chondrosarcoma (CS) is the second most common bone tumor affecting adults in their fifth decade of life. Although the appendicular skeleton is the site of occurrence, chest wall involvement has also been reported. They can be primary if it develops de novo or secondary if originates from a pre-existing benign lesion. Osteochondroma, enchondroma, synovial chondromatosis, and Paget’s disease are the common precursor lesions. A 24-year-old male with a history of chest wall tumor for which excision was done 11 years back presented with a recurrence at the same site. A past biopsy reported it to be chondroblastoma. Radiological investigations revealed the recurrence likely to be a CS. The patient underwent left thoracotomy and excision of the mass along with a segment of the sixth and seventh ribs from where the mass was arising. The biopsy reported well-differentiated CS. Since it was low-grade and most were resistant to chemotherapy and radiotherapy, no adjuvant therapy was given. Although uncommon for age and site, CS should be suspected even if the earlier excision biopsy was a benign cartilaginous tumor. Complete excision is the best treatment.